Grafixmoon: poster designing service / Ereena Elieya Azrin Irzal and Diana Othman - Azrin Irzal, Ereena Elieya; Othman, Diana (Academy of Language Studies, 2023)
Grafixmoon: Poster Designing Service is a project that is developed to assist people in advertising at reasonable costs and to create a platform to market artworks, particularly poster designs. A person's knowledge of desktop publishing, such as their graphic design and editing abilities, can be increased by producing posters from scratch and incorporating creative aspects. Before creating the poster, research must be done, and the content must be written based on the needs of the clients. This will also help to increase vocabulary and improve grammatical understanding. To determine the target market for this business, their range of spending for this service, and the kind of posters that they are interested in requesting, an online survey was conducted. Online platforms such as Instagram and WhatsApp were used to advertise this project, along with direct client interaction and negotiation. A feedback form was made to discuss the results and the aspects that can be improved in this project. Overall, the customers were mostly satisfied with the outcomes of the project requested which include the design, customer service, price and punctuality.